(untitled) (Universal International Scientific Journal, 2026)
This article discusses the issues of improving kinesthetic development in the process of preparing students for professional activity in a globalization and digital educational environment. The study analyzes the role of family psychology, gender stereotypes, mental health, and pedagogical erudition based on an integrative approach. A methodological system is justified to improve the quality of education and the effectiveness of professional training through the development of kinesthetic competencies.